EXTRACTION AND CHARACTERIZATION OF PECTIN FROM PASSION FRUIT (PASSIFLORA EDULIS L.) USING CHLORIDE ACID SOLUTION - Gatot Siswo Hutomo; Amalia Noviyanty; Ririn Kristianingsih (Universitas Tadulako, 2022)
Pectin is a natural substance found in most food crops. In general, pectin extraction uses mineral and organic acids, such as sodium hexametaphosphate acid, sulfuric acid, hydrochloric acid, acetic acid, nit citric, and citric acid. The study aimed to obtain the concentration of HCl, which gave the best value for the physical and chemical properties of passion fruit pectin. This study was a completely randomized design. The tested factor was 400 ml HCl solution with five treatment levels of HCl concentration: 1 N; 1.5 N; 2 N; 2.5 N; and 3 N. Each treatment was repeated three times, and therefore 15 experimental units were tested. The variables observed were pectin yield, methoxyl content, galacturonic content, esterification degree, clarity, water content, and ash content. The results showed that the 2.5 N HCl concentration resulted a yield value of 27.47%, methoxyl content 5.20%, galacturonic content 121.62%, esterification degree 24.26%, clarity 14.65%, water content 4.37 %, and 0.54% ash content, so the 2.5 N HCl concentration was the HCl concentration that gave the best effect on the physical and chemical properties of passion fruit pectin extraction.